MTT assay technique - Ashour, Abdelkader Elbadawy Abbas (2018)
Measurement of cell viability & proliferation forms the basis for numerous in vitro assays of a cell population’s response to external factors. -MTT assay was the first widely accepted method that replaced the radioactive tritiated thymidine incorporation assay to measure cell proliferation -Use of the MTT tetrazolium compound to measure the number of viable cells in culture was first described by Mosmann in 1983, with the modifications suggested by Denizot & Lang in 1986